2011
DOI: 10.1099/jmm.0.028225-0
|View full text |Cite
|
Sign up to set email alerts
|

Microbial biofilms on the surface of intravaginal rings worn in non-human primates

Abstract: Millions of intravaginal rings (IVRs) are used by women worldwide for contraception and for the treatment of vaginal atrophy. These devices also are suitable for local and systemic sustained release drug delivery, notably for antiviral agents in human immunodeficiency virus pre-exposure prophylaxis. Despite the widespread use of IVRs, no studies have examined whether surfaceattached bacterial biofilms develop in vivo, an important consideration when determining the safety of these devices. The present study us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 41 publications
2
39
0
Order By: Relevance
“…Mucosal levels of the proinflammatory cytokines remained stable throughout the study period in all animals, with no statistically significant changes being observed as a result of the IVRs. This is typical and has been observed previously in pig-tailed macaques with pod-IVRs (15,24).…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Mucosal levels of the proinflammatory cytokines remained stable throughout the study period in all animals, with no statistically significant changes being observed as a result of the IVRs. This is typical and has been observed previously in pig-tailed macaques with pod-IVRs (15,24).…”
Section: Discussionsupporting
confidence: 57%
“…The study timeline and biological sample collection points are shown in Fig. 2 and employed published protocols (15,24). Briefly, six sexually mature female pig-tailed macaques (Macaca nemestrina) were used; three received TDF-FTC IVRs (Table 1), and three received TDF-FTC-MVC IVRs.…”
Section: Materials Tenofovir Disoproxil Fumarate (Tdf) and Emtricitamentioning
confidence: 99%
See 1 more Smart Citation
“…For microflora analysis, vaginal swabs were collected from each macaque, placed into a Port-ACul tube, and transported on ice within 24 h of collection to MageeWomen's Research Institute (Pittsburg, PA) for microbial culture analysis. The presence of anaerobic and aerobic microorganisms was determined as described previously (19).…”
Section: Test Productsmentioning
confidence: 99%
“…Safety analyses of macaque-sized elastomeric silicone and polyurethane intravaginal rings (IVRs) loaded with candidate ARV drugs were tested in pig-tailed macaques in four studies ranging in duration from 49 to 73 days with retention of the IVR being 28 days in each study. The presence of IVRs not only made of silicone but other polymers such as, polyurethane in pig-tailed macaques does not cause an alteration longitudinally in the levels of the proinflammatory cytokines locally or systemically and in the vaginal microbiological patterns [225,226]. Efficacy studies in the NHP model with IVRs are just beginning, but preliminary pharmacokinetic studies are very promising [227][228][229][230][231][232][233][234][235].…”
Section: Drug Delivery Vehiclesmentioning
confidence: 99%